Comparison of the Effects of Public and Private Health Expenditures on the Health Status: a Panel Data Analysis in Eastern Mediterranean Countries - Enayatollah Homaie Rad; Sajad Vahedi; Abedin Teimourizad; Firooz Esmaeilzadeh; Mohamad Hadian; Amin Torabi Pour (Kerman University of Medical Sciences, 2013)
BackgroundHealth expenditures are divided in two parts of public and private health expenditures. Public health expenditures contain social security spending, taxing to private and public sectors, and foreign resources like loans and subventions. On the other hand, private health expenditures contain out of pocket expenditures and private insurances. Each of these has different effects on the health status. The present study aims to compare the effects of these expenditures on health in Eastern Mediterranean Region (EMR). MethodsIn this study, infant mortality rate was considered as an indicator of health status. We estimated the model using the panel data of EMR countries between 1995 and 2010. First, we used Pesaran CD test followed by Pesaran's CADF unit root test. After the confirmation of having unit root, we used Westerlund panel cointegration test and found that the model was cointegrated and then after using Hausman and Breusch-Pagan tests, we estimated the model using the random effects. ResultsThe results showed that the public health expenditures had a strong negative relationship with infant mortality rate. However, a positive relationship was found between the private health expenditures and infant mortality rate (IMR). The relationship for public health expenditures was significant, but for private health expenditures was not. ConclusionThe study findings showed that the public health expenditures in the EMR countries improved health outcome, while the private health expenditures did not have any significant relationship with health status, so often increasing the public health expenditures leads to reduce IMR. But this relationship was not significant because of contradictory effects for poor and wealthy peoples.